Penerapan Edukasi Berbasis Discharge Planning untuk Peningkatan Pengetahuan Orang Tua pada Asuhan Keperawatan Bayi dengan Ileus Obstruksi Pasca Pembedahan di Rsup Prof. Dr. R.D Kandou Manado - Tambengi, Henny; Gannika, Lenny; Simanjuntak, Susi Roida (Mapalus Nursing Science Journal, 2024)
Background: Obstructive ileus is a condition where the contents of the gastrointestinal lumen cannot be channeled distally due to a blockage or mechanical obstacle caused by abnormalities in the intestinal lumen, intestinal wall, or outside the intestine, which presses on or causes vascularization abnormalities in an intestinal segment, which causes intestinal segment necrosis. the. In children who have been diagnosed with obstructive ileus, surgery must be carried out immediately at any time; otherwise, it can cause various complications. When a child has had surgery, parents have a very big role in being able to care for the child after surgery. Therefore, parental knowledge is one of the factors in the success of child care. Objective: To determine the effectiveness of discharge planning-based education in increasing parental knowledge. Method: This study used a case study method with the implementation of discharge planning-based education regarding post-surgical obstructive ileus infant care at home for 3 days. Results: After conducting education based on discharge planning for 3 days, it was found that parents' knowledge increased regarding caring for babies with post-surgical obstructive ileus at home. Conclusion: Education based on discharge planning for parents has been proven to increase parents' knowledge regarding caring for babies with post-surgical obstructive ileus at home. Keywords: Education, Discharge Planning, Parents, Knowledge